Lira Costeña de Maquilon - Torres, Martin (Revista Universidad de Guayaquil, 1998)
Don CESAR MAQUILON, poet of the portwho adorned balconies with his verse,from this Guayaquil, with an open heart,makes the idyll eternal with his poetry. The tropical lyre, Guayaquil’s own, fullof the bard Maquilón, tree and accent,has the freshness of a woman, lover, eternal,longings in bloom, carnal monuments.